Redes de interações entre aves frugívoras e plantas em uma área de Mata Atlântica no sudeste do Brasil - Rodrigues, Suelen Barbosa Moraes (Universidade Federal de São Carlos, 2015)
Interactions plants-frugivores are key components in the complexity of forest communities and their modifications or losses can have profound implications for conservation. The study of the interactions networks has proven an important tool in understanding how communities respond to human disturbance. The aim of this study was to analyze the interactions networks between plants and birds as fruit consumers in Atlantic Forest in southeastern Brazil. The research was conducted in Carlos Botelho State Park (PECB) and addressed three environments with different types of vegetation (open area, and initial successional stages and advanced). The interactions record was performed by direct observation using methods of transect, focal and assistance traps cameras. We evaluated the frequency of visits, number of interactions, nesting and connectance. The network is represented by 63 kinds of birds and 30 species of plants and showed a nested pattern (NODF = 33.63, p = 0) with a connectance low (13%). 255 interactions were observed in 1151 records frugivory. The species that contributed most to the organization's network were also the most important for community maintenance and alien species present in one of the rooms did not interfere in the interactions between native species.
Interactions network between frugivorous birds and plants in an Atlantic Forest area in southeastem Brazil
Keywords: Ave; Birds; Sementes - Dispersão; Seeds - Dispersal; Ecologia trófica; Trophic ecology; Rede mutualística; Mutualistic network; Câmera trap; CIENCIAS BIOLOGICAS::ECOLOGIA